The mental health of Australian elite athletes - Gulliver, A.; Griffiths, K. M.; Mackinnon, A.; Batterham, P. J.; Stanimirovic, R. (Journal of Science and Medicine in Sport, 2015)
Objectives: Currently, little is known about the prevalence of mental disorders in athletes. This study aims to investigate Australian elite athletes` symptoms of general psychological distress and common mental disorders. Design: A cross-sectional survey design was employed to assess self-reported symptom prevalence. Methods: A total of 224 elite athletes (118 female, 106 male) from national sporting organisations in Australia were administered a self-report internet-based survey comprising measures of demographic status and mental health symptoms. Results: Overall, 46.4% of athletes were experiencing symptoms of at least one of the mental health problems assessed. Percentages meeting criteria for mental disorders were similar to previous epidemiological studies of both international athlete and community samples: depression (27.2%), eating disorder (22.8%), general psychological distress (16.5%), social anxiety (14.7%), generalised anxiety disorder (7.1%), and panic disorder (4.5%). Injured athletes had higher levels of both symptoms of depression (t = 3.23, p = .001) and generalised anxiety disorder (t = 2.26, p = .025). Conclusions: The level of symptoms of mental health problems reported by elite athletes appears similar to that observed in the community. However, caution must be exercised in interpreting the findings, as possible demographic differences between athletes and comparison population datasets may exist. Furthermore, self-selection of respondents in the present study may have reduced the representativeness of the sample and the validity of the comparisons. Athletes, particularly those currently injured, should be well-supported to seek help for mental disorders through access to mental health professionals.